Parameterization of two‐dimensional approaches in HYDRUS‐2D: Part 2. Solute transport at the field and column scale. Issue 5 (4th August 2021) - Varvaris, Ioannis; Pittaki‐Chrysodonta, Zampela; Duus Børgesen, Christen; Iversen, Bo Vangsø
Abstract: In this study, a tracer field experiment was conducted to study the temporal dynamics of bromide movement in a loamy tile‐drained agricultural landscape. Moreover, tritium leaching experiments were performed on undisturbed soil columns from the same field. The HYDRUS‐2D software package was used to model water and solute transport. Three water flow models developed in Part 1—a single‐porosity approach with modified soil hydraulic functions (SP), a dual‐porosity approach (DP), and a dual‐permeability approach (DUP)—were used as a foundation for building solute transport models, of which the initial parameterization was based on a suggested hydrogeological tool from previous studies. The selected solute transport models were an SP, an SP with immobile water, a DP, a DUP, and a DUP with immobile water. The model predictions were compared against measurements of bromide concentrations in soil‐water. The DP captured the degree of the initial peaks and predicted well the shape of the observed concentrations. However, DP presented low capability to match the timing of bromide concentration peaks. In contrast, the DUP with immobile water illustrated better predictive ability by introducing an additional pore region into the matrix domain. Validation of field‐scale solute transport models was implemented using the data from the following leaching experiments. The already suggested parameterization concept was further evaluated for its capability to provide a sufficient initial representation of the internal pathways. The output from such hydrogeological studies shows that macropores and their interconnection with tile drains are key to understanding the water flow and solute transport processes in loamy structured soils. Core Ideas: A bromide tracer field experiment was simulated. A suggested hydrogeological tool for parameterizing soil hydraulic properties was expanded and evaluated. Solute transport models were validated utilizing tritium leaching experiments at the column scale. The direct connectivity between macropores and tile drains was evaluated.